Exploring Approaches and Motivations of Plays on Words in Enterprise Names in Yogyakarta - Putu Wijana, I Dewa; Yoga, Adwidya (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
This article was initially triggered by the use of ‘plays on words’ found in enterprise naming around Yogyakarta. Based on that phenomenon, this article focused on approaches and motivations of enterprises naming using plays on words, influences of foreign languages used as naming models, and their semiotic interpretations. The data were collected were in the forms of enterprise names suspected to have been created as plays on words by observing enterprises’ billboards and placards around Yogyakarta. The data were also gained by interviewing several enterprise owners to reveal the motivations underlying the use of plays on words. The collected data were analyzed to unveil the closest pronunciations, meanings, and spelling of the names of enterprises influenced by various context, such as the products yielded, services offered, environments, location of enterprises, etc. This article found that naming practices involve several approaches, i.e., spelling deviations, homo phonic and nearly homo phonic pairing, spelling permutations, contractions, and word-to-word translation. There were at least six foreign languages used as models, namely English, French, Italian, Japanese, Mandarin, and Arabic. Two main motivations were identified for these naming practices: to create jokes and to lend beauty. From a semiotic viewpoint, these phenomena constitute struggles of the dominated group, whose language is socially less prestigious, against the dominant group, whose language is considered more prestigious. It implies that using plays on words strategy in naming enterprises can be seen as a branding strategy to generate jokes or fun names and to lend beauty which in the end impact in persuading target market to visit their business enterprises.